Censorship: Social media, including X/Twitter, Facebook, Instagram and Y (Pakistan) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Pakistan. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2024-0002. Severity: warning. Confidence: 75%